Feast or Famine: Harvest yields, sustainable livelihoods and climate variability in Vhembe district, Limpopo, South Africa - McFarlane, Lloyd (My University, 2017)
The objective of the thesis was to determine the relationship between climate variability and rural livelihoods in the Vhembe District Municipality situated in the extreme north of South Africa. These relationships ranged between food and nutritional security, land tenure, financial security, domestic politics and their impacts on human well-being in terms of the Sustainable Livelihoods Framework. The thesis uses a multi-discipline approach to assess the socio-economic outcomes of poor support to rural households that are struggling to attain an acceptable standard of living in the face of increasing challenges brought about by climate change. It also looked to investigate the capacity of rural households to adapt to the challenges of living in such an area. Results were obtained through questionnaires and basic interviews conducted among the residents of three selected areas in the Vhembe District of South Africa. The results demonstrate that residents of Vhembe go through daily suffering as a result of poor support and assistance in adapting to the challenges of climate change in the area and its impact on their livelihoods. The on-going academic literature suggests that integrated livelihood resilience is essential to adaptation to climate variability and that this can reduce the vulnerability of these areas. It also calls for the development and maintenance of effective local institutions supported by public private partnerships. Gaps identified in the literature suggested that more knowledge on land use change caused by seasonal variability as a result of the El Niño Southern Oscillation was needed as well as the prevalence of indigenous knowledge systems in adapting to these changes. It was found that local knowledge and effective local institutions were not as prevalent as expected in achieving livelihood adaptation. Some key findings were that 59% of households did not have access to arable land with 49% of respondents stating that they did not plant crops in the recent season due to the poor rains experienced. Furthermore, the reliance on social grants was notably high with 32% of respondents relying on these. Some residents who cannot pay to have access to electricity are forced to collect or buy firewood for everyday use. Furthermore, only 9% of respondents stated that they had access to flush toilets. These issues are shown to have environmental and other social consequences in the target communities. The thesis concludes that management of natural resources in Vhembe needs to be improved, as these are potential safety nets for the rural poor. It also suggests that there will need to be more support by government and business to set up beneficial agricultural projects to sustainably grow inclusive prosperity for rural residents of the Vhembe District. Key Words: Climate Variability, Sustainable Livelihood Framework, Adaptive Capacity
Thesis (M.Sc. (Interdisciplinary Global Change Studies))--University of the Witwatersrand, Faculty of Science, School of Geography, Archaeology & Environmental Studies, 2017.
Keywords: Climatic changes; Economics--Social aspects; Rural development--South Africa--Limpopo; Climatic changes--Environmental aspects